2018
DOI: 10.1111/ijac.12879
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Al2O3 on the high‐temperature oxidation resistance of Si‐B‐C ceramic under air atmosphere

Abstract: Si‐B‐C ceramics were prepared through reaction sintering, and the influence of Al2O3 addition on the high‐temperature (1100‐1300°C) oxidation behavior of the material under air atmosphere was studied. The erosion behavior and mechanism are determined from the measurement of weigh changes, microstructure observations, and characterization of the generated oxides on postexposure specimens. Results show that Al2O3 is enriched in the oxidized layer, inhibiting the volatilization of B2O3 and impeding the crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The presence of viscous flow has an effect on filling the cracks and increasing the bonding strength between particles . Shao et al demonstrated that liquid phase Y 3 Si 2 C 2 could fill the pores in a SiC‐based ceramic during sintering, which promoted neck formation and grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of viscous flow has an effect on filling the cracks and increasing the bonding strength between particles . Shao et al demonstrated that liquid phase Y 3 Si 2 C 2 could fill the pores in a SiC‐based ceramic during sintering, which promoted neck formation and grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the phase of B 12 (B, C, Si) 3 was also not obviously shown in X-ray results ( Figure 6). In our previous study, 17 we found that B and C were the main elements of this black phase in addition of small amount of Al and Si. Figure 2 presents the microstructure of composites.…”
Section: Materials Preparationmentioning
confidence: 61%
“…Fortunately, Al 2 O 3 can be dissolved in glass phase in cracks (Figure 5I). It can increase the viscosity of glass phase and inhibit the oxidizing medium from diffusing along the crack into internal material 17,21 . Table 1 summarizes the cracks healing property of typical boron‐containing self‐healing composites under different test condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations